Evaluasi Redesain Antarmuka SIPP Berbasis SUS dan Figma terhadap Kepuasan Pengguna (Studi Kasus pada Salah Satu Pengadilan Negeri 1B) - Sultan Zathnani Tubagus; Rukhviyanti, Novi (Jurnal Ragam Pengabdian, 2026)
This study aims to evaluate the usability level of the Sistem Informasi Penelusuran Perkara (SIPP) interface, systematically identify interface problems, and redesign the interface based on user experience using Figma with the Design Thinking framework. The research employed a mixed methods approach that integrated quantitative measurement through the System Usability Scale (SUS) questionnaire involving 110 active users, as well as qualitative analysis through observations and in-depth interviews. The results showed that the average SUS score was 70.09, which falls into the OK category, Grade C, and Acceptable level. However, several aspects still require improvement, particularly in the initial user adaptation stage. Item analysis indicated that learnability was the system’s main strength, while the need for initial adaptation became its primary weakness. Data triangulation identified five priority issues, namely menu navigation, search features, visual appearance, system speed, and the availability of contextual guidance. Based on these findings, a redesign process was carried out, resulting in an interactive high-fidelity prototype as a more user-oriented solution. This study is expected to provide practical contributions to improving the quality of digital administrative services in Indonesia.